RESPONSE TO "RESISTANCE AND SENSITIVITY PATTERN OF STAPHYLOCOCCUS AUREUS: A STUDY IN LADY READING HOSPITAL, PESHAWAR" - Bari, Fazli (Journal of Postgraduate Medical Institute, 2013)
I have been following the progress ofJPMI for quite some time and am very glad withits growth. It is definitely an inspiring journalwhich supports research, especially in Pakistan.